Saving determinants in Malaysia - Hafizah Hammad Ahmad Khan,; Hussin Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Saving is an important indicator of economic development where it is viewed as an element which finances domestic investment to achieve economic growth. The purpose of this paper is to examine the saving determinants in Malaysia. By using Life Cycle Model setting, this study employs a saving function which includes per capita income, rate of returns on savings deposit, government fiscal balance, young age dependency rate, and old age dependency rate and also inflation rate as the potential determinants of saving. The results showed that per capita income, rate of returns, old age dependency and inflation rate are the determinants of national savings while per capita income, rate of returns, government fiscal balance, young age dependency, old age dependency and inflation rate are the determinants for private saving in a long run. In a short run we found that per capita income, government fiscal balance and young age dependency are the significant determinants of national saving in a short run while private saving determinants are found to be per capita income, rate of return and young age dependency. Furthermore, variable ECM which indicates the speed of adjustment shows that more than 75% of the adjustment is completed in a year for national saving determinants, while more than 86% of the adjustment is completed in a year for private saving determinants. Results obtained in this study suggest that policy makers should monitor all significant variables since they give impact on the savings rate.